True Followers of Justice : Identity, Insertion and Itinerancy among the Early Franciscans - Warner, Keith; Cusato, Michael F.; Saggau, Elise (Spirit and life (Saint Bonaventure, N.Y.), 2000)
As thirteenth-century urban populations increased, the friars, entrusted by the Church with the ministry of preaching, naturally needed to go where the people were. At the same time they needed to honor their way of life, which required them to live prayerfully in fraternities, yet not settle down permanently in stable religious houses after the monastic model. Cusato and Warner present issues arising from this tension and look at how the Order did, and still does, attempt to resolve it or at least live creatively with it.